Design and Implementation of the State Monitoring and Balancing Management of Vehicle Power Battery. (May 2017) - Fang, Linlin; Li, Jun-qiu; Shi, Wentong
Abstract: The voltage, thermal and consistency of the battery have great influence on the working performance and service life of the battery, so battery state monitoring and balancing management is very necessary. In this paper, based on the chip LTC6802 and CS5460A, the battery monomer voltage, total voltage, charge and discharge current and battery temperature are monitored. A model of inconsistency evaluation is established and battery whether needs to be balanced is determined by balancing strategy. The resistance equalization method and the chip LT1513 are combined to realize bidirectional battery equalization.